A reflection of the Ottoman Empire in the poetry of Ahmad Shawki - Kozhabekova, R.S. (Journal of Oriental Studies, 2023)
Egypt is the most important region of the east-west route, the Mediterranean basin, which opens to the west. Because of its location as a gate, it has drawn the interest of major states in every century and has been the center of attention. Because of Egypt’s strategic importance in the 19th century, France and England pursued colonial interests in the nation. In this country, both European governments’ colonial actions in Egypt, as well as Egypt’s isolation from the Ottoman Empire, have an impact. It also influenced the creation of diverse thinking currents. Among them were Egyptian intellectuals and their views on the caliphate, as well as the formation of distinct understandings of nationality. The influence of Islamism and nationalism was deeply felt on Egypt and the intellectuals living in this country. We picked Ahmad Shawki, one of Egypt’s thinkers, since he is an Arab of Turkish descent who dedicated himself to the Ottoman empire during the time of Abdul-Hamid II. The notion of nationalism was seen in Egypt in a variety of ways throughout this time. “Egyptian Nationalism Related to the Ottoman Caliphate” was Ahmad Shawki’s definition of nationalism. Because he is devoted to the caliphate, he has the notion of Islamic Union; Ahmad Shawki is a nationalist thinker who loves Egypt, and the idea of Islamic unity and nationalist element is the major focus of this research.